2016
DOI: 10.7196/samj.2016.v106i2.9870
|View full text |Cite
|
Sign up to set email alerts
|

Empirical antimicrobial therapy for probable v. directed therapy for possible ventilator-associated pneumonia in critically injured patients

Abstract: Background. Ventilator-associated pneumonia (VAP) has recently been classified as possible or probable. Although direct attributable mortality has been difficult to prove, delay in instituting appropriate therapy has been reported to increase morbidity and mortality. Recent literature suggests that in possible VAP, instituting directed therapy while awaiting microbiological culture does not prejudice outcome compared with best-guess empirical therapy. Objectives. To ascertain outcomes of directed v. empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…25 Antimicrobials may not be necessary, and due to its inherent multi-drug resistance our policy is not to institute treatment if found with other pathogens. 26 In the presence of sepsis and if Acinetobacter baumannii is the sole isolate, then therapy is commenced as it may be pathogenic. 27 If regarded as colonization, the incidence of sepsis-related complications may have been overestimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…25 Antimicrobials may not be necessary, and due to its inherent multi-drug resistance our policy is not to institute treatment if found with other pathogens. 26 In the presence of sepsis and if Acinetobacter baumannii is the sole isolate, then therapy is commenced as it may be pathogenic. 27 If regarded as colonization, the incidence of sepsis-related complications may have been overestimated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…data confirm that this distinction remains useful when deciding upon empiric therapy. 11 In our study it was observed that community acquired flora susceptible to amoxycillin/clavulanate accounted for the vast majority of pathogens isolated in early VAP. Suggestions that the distinction between early and late VAP should be abandoned emanate from the developed world where widespread antimicrobial use has led to a high level of bacterial resistance within the community.…”
Section: Discussionmentioning
confidence: 62%
“…Although the isolated flora may be similar in intensive care units the extent and specifics of bacterial resistance to antimicrobials varies considerably, the most common reasons are prior antimicrobial exposure, the overuse of broad spectrum agents and selective pressure. 11 Despite suggestions that the differentiation between early and late VAP is irrelevant and that all patients should be treated with broad spectrum agents, 16 our Funding -No funding has been received.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Quality improvement initiatives in which clinicians empirically prescribed antibiotic therapy only for patients with signs of possible sepsis but waited for confirmatory data before prescribing for those without sepsis suggest that this strategy is not only safe but may even confer a mortality benefit. [35][36][37][38] Similarly ranges. [21][22][23] Integrating serial procalcitonin monitoring may further facilitate this strategy.…”
Section: Resultsmentioning
confidence: 88%